«
  
»

]Gente .

1) Calcule:

a) x²-2x=x+4

b)x. (x+11)+2.(x+21)=0

c) x²-2x=2x-4

d)9x²+3x+1=4x²

e)x²+10=9x-10



RESOLVENDO

A)x²-2x-x-4=0=x²-3x-4=0(equação ax²+bx+c=0)
x=[{(-b)+/-Raiz quadrada(b² -4. a. c)}/(2a)]
x=[{(-(-3)+/-Raiz quadrada((-3)² -4.1.(-4))}/(2.1]
x1=[{(3)+Raiz quadrada(25}}/(2)]=[3+5]/2=4
x2=[{(3)-Raiz quadrada(25}}/(2)]=[3-5]/2=-2/2=-1
V={-1,4}
b)b)x. (x+11)+2.(x+21)=0=x. x+x. 11+2. x+2.21=0=x²+11x+2x+42=x²+13x+42=0
x=[{(-b)+/-Raiz quadrada(b² -4. a. c)}/(2a)]
x=[{(-(13)+/-Raiz quadrada((13)² -4.1.(42))}/(2.1]
x1=[{(-13)+Raiz quadrada(169-168}}/(2)]=[-13+1]/2=-12/2=-6
x2=[{(-13)-Raiz quadrada(1}}/(2)]=[-13-1]/2=-14/2=-7
V={-6,7}
c) x²-2x=2x-4 ; x²-2x-2x+4=0=x²-4x+4=0
x=[{(-b)+/-Raiz quadrada(b² -4. a. c)}/(2a)]
x=[{(-(-4)+/-Raiz quadrada((-4)² -4.1.(4))}/(2.1]
x1=[{(+4)+Raiz quadrada(16-16}/(2)]=[4+0]/2=4/2=2
x2=[{(+4)-Raiz quadrada(16-16}}/(2)]=[4-0]/2=4/2=2, ou seja, x1=x2=2
V={2}
d)9x²+3x+1=4x²; 9x²-4x²+3x+1=0=5x²+3x+1=0
x=[{(-b)+/-Raiz quadrada(b² -4. a. c)}/(2a)]
x=[{(-(3)+/-Raiz quadrada((-3)² -4.5.(1)}/(2.5)}]
como não  existe Raiz quadrada({(9 -20)}=Raiz quadrada({(-11)}  nos conjuntos dos reais(não existe nos reais, qualquer raíz quadrada de número negativo, no caso, o -11)
V={Vazio}
e)x²+10=9x-10; x²+10-9x+10=0=x²-9x+20=0
=[{(-b)+/-Raiz quadrada(b² -4. a. c)}/(2a)]
x=[{(-(-9)+/-Raiz quadrada((-9)² -4.1.(20))}/(2.1]
x1=[{(9)+Raiz quadrada(81-80)}/(2)]=[9+1]/2=5
x2=[{(9)-Raiz quadrada(81-80}}/(2)]=[9-1]/2=8/2=4
V={4,5}



TAREFAS SIMILARES: